Minimally invasive 1,444-nm Nd:YAG laser treatment for axillary bromhidrosis - Piccolo, Domenico; Mutlag, Mohammed Hussein; Pieri, Laura; Fusco, Irene; Conforti, Claudio; Crisman, Giuliana; Bonan, Paolo (Frontiers in Medicine, 2023)
Background: Axillary bromhidrosis is an apocrine glands hyperactivity disease. Methods: 24 patients (15 men and 9 women) with axillary bromhidrosis underwent laser procedure with a Nd:YAG laser emitting at 1,444 nm. Parameters evaluated in this study were: the degree of malodor (T0 baseline; T30 after 1 month; T180 after 6 months), postoperative pain and short-term decreased mobility (T1 after 1 day; T7 after 7 days; T30 after 1 month), as well as overall satisfaction (T30 after 1 month; T180 after 6 months). A visual analog scale (VAS), from 0 to 10, was used to assess pain and decreased mobility, with lower values denoting less severity. Results: 24 patients were followed-up for 6 months after laser treatment. At baseline all patients (100%) complained of a strong axillary malodor (mean degree of malodor at T0=2.0±0.00). It decreased to 0.50±0.64 at T30. At T180 the degree of malodor was 0.54±0.57. Both T30 and T180 degrees of malodor significantly decreased from the baseline value (p<0.01). The mean degree of patient satisfaction at T30 was 1.75±0.52 and at T180 was 1.67±0.21. Among the 24 patients, 8 complained of moderated pain 1 day after treatment. The pain had subsided at day 7 except for 2 patients with VAS = 1. Pain and mobility restrictions were in any case resolved within T30. Conclusion: Treatment with a 1,444 nm Nd:YAG laser for subdermal interstitial coagulation could be a less invasive and more effective option treatment for axillary bromhidrosis.